2018
DOI: 10.1080/09593985.2018.1455251
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy management of patients with chronic pelvic pain (CPP): A systematic review

Abstract: The evidence currently available is sparse with methodological flaws, making it difficult to recommend a specific physiotherapy option. There is an urgent need for high-quality randomized controlled trials to identify the most effective physiotherapy management strategy for patients with CPP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 67 publications
1
49
0
6
Order By: Relevance
“…Physical therapy to the pelvic region was focused on imparting patient control of the muscle relaxation and contraction processes, which may contribute to improving muscle relaxation and consequently to changing the muscle width. e literature supports such a causative linkage, as studies have reported a lengthening of the levator ani muscle following MPT in CPPS patients that was correlated with the degree of improvement in clinical pain ratings [45,77,78]. e current study did not compare the muscle length and width between women with CPPS and healthy women, which eliminates the possibility to derive any conclusions about a possible anatomical impairment in the muscle prior to the intervention.…”
Section: Discussionmentioning
confidence: 75%
“…Physical therapy to the pelvic region was focused on imparting patient control of the muscle relaxation and contraction processes, which may contribute to improving muscle relaxation and consequently to changing the muscle width. e literature supports such a causative linkage, as studies have reported a lengthening of the levator ani muscle following MPT in CPPS patients that was correlated with the degree of improvement in clinical pain ratings [45,77,78]. e current study did not compare the muscle length and width between women with CPPS and healthy women, which eliminates the possibility to derive any conclusions about a possible anatomical impairment in the muscle prior to the intervention.…”
Section: Discussionmentioning
confidence: 75%
“…As another example, we did not include any of the maternal, urological or gynecological, even though there is a body of literature pointing that physical therapy can be useful for addressing incontinence and pelvic pain [70,71]. However, we found that underlying evidence base on use of physical therapy for on the chronic pelvic pain and incontinence still is considered insufficient [72,75], and the vast majority of urological and gynecological conditions are not typically treated with physical rehabilitation. In addition, data weren't available in the GBD to identify particular urological/gynecological conditions potentially amenable for rehabilitation, i.e., there are no GBD "impairments" for consequences of such as urological/gynecological conditions such as incontinence or pelvic pain.…”
Section: Data Selectionmentioning
confidence: 99%
“…Comparing the study intervention with non-standardized physical therapy can be considered a limitation because of the heterogeneous treatment. However, there is no consensus on a standardized physical therapy approach in CPP, 6 and comparing the intervention with the "usual treatment" offered to these women provides real-world clinical data. Furthermore, the lack of blinding of the data collectors and patients is a limitation, and there might be a selection bias because one-third of the eligible women declined to participate.…”
Section: Discussionmentioning
confidence: 99%
“…2 A systematic review of physical therapy treatment for CPP summarized that positive results can be achieved with single modalities such as manual techniques and exercises, but the evidence is limited. 6 Physical therapy focusing on body awareness and cognitive techniques has been highlighted as a promising therapy, and a future avenue for research in CPP. 6 Group-based physical therapy is considered time saving and cost efficient; it can be as effective in reducing pain as individual treatment and can provide social affinity for the participants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation